SOL-GEL THIN FILM BASED SENSORS AND BIOSENSORS - VIDHYA.S; BHASKAR MOHAN MURARI (International Journal of Pharma and Bio Sciences, 2016)
A wide variety of enhanced and modified sol-gel bulk and thin film processes for the development of sensors and biosensors have been witnessed in the last two decades. The porous silica glass material prepared by the sol-gel process is a promising host matrix for the encapsulation of various biomolecules viz. proteins, antibodies, enzymes. The entrapped biomolecules have shown to retain their functionality in the sol-gel matrix just like in solution by retaining their inherent properties. Therefore, this property of sol-gel has been widely utilized to form sensitive layers for sensing pH, gases, biomarkers, ionic species and solvents. Sol-gel derived thin films with entrapped biomolecules have been used as bio-recognition element for development of biosensors. The biosensors developed so far, has exhibited favorable sensitivity and response time towards the target analytes. The present review focuses on research carried out in the past years for the development of sensors and biosensors using sol-gel thin film entrapped biomolecules and their utilization as a sensitive membrane / bio-recognition elements for the construction of highly selective biosensors.